Dupilumab treatment ameliorates clinical and hematological symptoms, including blood eosinophilia, in patients with atopic dermatitis. (29th September 2020) - Yamauchi, Teruo; Sasaki, Shun; Lee, Eun Seon; Tamura, Takayuki; Seki, Marina; Miwa, Tasuku; Kobayashi, Kae; Saruta, Yusuke; Kitami, Yuki; Sueki, Hirohiko; Watanabe, Hideaki
Abstract: Background: Atopic dermatitis (AD) is an allergic disease that affects individuals of various ages. Recently, the IL‐4/13 inhibitor dupilumab has gained regulatory approval for clinical use in AD patients. Dupilumab has been reported to reduce several markers of AD, including the serum levels of thymus and activation‐regulated chemokine (TARC/CCL17), blood lactate dehydrogenase (LDH), and serum total immunoglobulin E (IgE). Methods: We retrospectively reviewed data from 40 AD patients who were treated with dupilumab. Eczema Area and Severity Index (EASI), Investigator's Global Assessment (IGA), body surface area (BSA) scores, TARC, LDH, total IgE, and eosinophil count in peripheral blood were assessed for a total of 32 weeks. Results: The EASI, IGA, and BSA scores improved significantly with treatment, indicating a reduction in AD severity. Serum TARC and LDH levels also significantly decreased with treatment. Serum IgE levels were unchanged at 2 weeks of treatment but decreased significantly between 4 and 32 weeks. The number of eosinophils in the peripheral blood decreased at 4, 16, and 32 weeks after treatment initiation. Conclusions: Several studies have reported that serum TARC, LDH, and total IgE levels are reduced by dupilumab treatment. Our real‐world data are the first to demonstrate a reduction in blood eosinophilia in patients who receive clinical treatment with dupilumab.